2011
DOI: 10.1371/journal.pone.0026108
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Proteomic and Metabolomic Analysis of an Artificial Microbial Community for Two-Step Production of Vitamin C

Abstract: An artificial microbial community consisted of Ketogulonicigenium vulgare and Bacillus megaterium has been used in industry to produce 2-keto-gulonic acid (2-KGA), the precursor of vitamin C. During the mix culture fermentation process, sporulation and cell lysis of B. megaterium can be observed. In order to investigate how these phenomena correlate with 2-KGA production, and to explore how two species interact with each other during the fermentation process, an integrated time-series proteomic and metabolomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 41 publications
3
71
0
Order By: Relevance
“…According to our previous study, the purine biosynthesis was weak in K. vulgare, but it could be enhanced by the co-culturing with B. megaterium [15]. From the proteomic study of experimental evolution in this study, we found the biosynthesis of purine and pyrimidine was improved in the evolved K. vulgare in the co-culture.…”
Section: Resultssupporting
confidence: 54%
“…According to our previous study, the purine biosynthesis was weak in K. vulgare, but it could be enhanced by the co-culturing with B. megaterium [15]. From the proteomic study of experimental evolution in this study, we found the biosynthesis of purine and pyrimidine was improved in the evolved K. vulgare in the co-culture.…”
Section: Resultssupporting
confidence: 54%
“…Recent studies demonstrated that Bacillus sp. could release metabolites in amino acid biosynthesis (Liu et al, 2011a;Zhou et al, 2011) and purine during cell lysis upon sporulation Ma et al, 2011;Zhang et al, 2010), which can be used to compensate the deficient metabolism of K. vulgare (Zou et al, 2012). In this study, our results showed that the blank plasmid did not impair the growth and 2-KLG production in the consortium of K. vulgare-B.…”
Section: Effect Of Overexpression Of Endogenous L-sorbose Pathway On mentioning
confidence: 52%
“…However, the need to use a mixed fermentation system for 2-KLG production by K. vulgare and B. megaterium makes traditional screening methods for K. vulgare mutants capable of 2-KLG overproduction laborious and complicated, 7 leading to a much lower screening efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…K. vulgare contains a complete enzyme system for converting l -sorbose to 2-KLG, 4 but its growth is poor in the monoculture, resulting in a very low yield of 2-KLG 5 . A companion strain, Bacillus megaterium , is generally considered to generate and release, in the fermentation broth, the metabolites that stimulate K. vulgare propagation and 2-KLG accumulation 6, 7, 8, 9, 10. These metabolites contain active proteins, 6 amino acids, 8 antioxidants, 10 and other active substrates 7, 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation